1987
DOI: 10.1111/j.1432-1033.1987.tb13327.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and in vitro synthesis of the Dolichos biflorus seed lectin

Abstract: The Dolichos bzflorus seed lectin contains two structurally related subunits. A cDNA library was constructed using RNA isolated from D. bijlorus seeds actively synthesizing the seed lectin. The library was expressed in Escherichia coli using a lambda Charon 16 vector, and lectin-specific antiserum was used to isolate a seed lectin cDNA. Hybridization of the D. bzflorus seed lectin cDNA to RNA isolated from seeds actively producing both lectin subunits identifies a single-size RNA of 1100 bases. An oligodeoxyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The inhibition of glycosylation of the subunit precursors with tunicamycin is in agreement with evidence from previous in vitro biosynthetic studies that showed glycosylation to be a cotranslational event in the synthesis of this lectin (27). Such cotranslational glycosylation and subsequent posttranslational alteration of carbohydrate units have been found to be common features in the biosynthesis of many plant lectins (10,12).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The inhibition of glycosylation of the subunit precursors with tunicamycin is in agreement with evidence from previous in vitro biosynthetic studies that showed glycosylation to be a cotranslational event in the synthesis of this lectin (27). Such cotranslational glycosylation and subsequent posttranslational alteration of carbohydrate units have been found to be common features in the biosynthesis of many plant lectins (10,12).…”
Section: Discussionsupporting
confidence: 89%
“…This finding, coupled with structural studies on the subunits (7,8,15,25,26) and the finding of only a single seed lectin mRNA and in vitro translation product (27), suggest that the precursor for subunit II may arise from the precursor for subunit I by carboxyl terminal proteolytic cleavage. Posttranslational proteolytic modifications have been found to occur during the biosynthesis of a number of seed lectins and storage proteins, however such processing events are usually associated with the protein bodies (10).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Maximum identity (93%) was observed with a group of uncharacterized legume lectins from Phaseolus filiformus and Phaseolus parvulus. The list includes the well studied DBL and DB58 of Dolichos biflorus [22].…”
Section: Internal Peptide Sequence Of Purified Ppomentioning
confidence: 99%
“…Consistent with such a hypothesis is the fact that these homologous sequences map at the surfaces of the molecules of proteins for which three-dimensional structures are known. [36], Dolichos seed lectin (DBS) [37], Dolichos cell-wall-associated lectin (DB58) [38], Diocleu lectin [39], Lathyrus ochrus lectin [40], arcelin 2 [41], soybean Kunitz trypsin inhibitor [42], Erytrina Kunitz-type trypsin inhibitor [43], winged bean Kunitz-type trypsin inhibitor [44], alfalfa wound-induced trypsin inhibitor [45], tomato protease inhibitor I1 [46], potato protease inhibitor I1 [47], carboxypeptidase Y [7], large T antigen of simian virus 40 [48], pBR322 8-lactamase [49].…”
mentioning
confidence: 99%